Pengaruh financial knowledge, lifestyle pattern pada perilaku manajemen keuangan wanita karir dengan locus of control sebagai variabel moderasi - Rendra Elvira Shinta; Wiwik Lestari (STIE Perbanas Surabaya, 2018)
Financial management behavior become a very important nowadays. This is related to the consumptive behavior in Indonesian and especially in Sidoarjo. The purpose of this reasearch was to determine The Impact Of Financial Knowledge, Lifestyle Pattern Of Career Woman Financial Management Behaviour With Locus Of Control As Moderating Variable.The sample consists of 180 respondents who have the characteristics as career woman that domiciled in Sidoarjo, has a income, as a manager of personal finances, productive age on 20-55 years, and at least junior high school as the latest education. Samples were selected using purposive sampling technique. Data were analyzed by Structural Equation Modeling on PLS (Partial Least Square). The results of this reasearch is represent that Financial Knowledge have a positive signficant impact on financial management behaviour, Locus of Control have a positive signficant impact on financial management behaviour and Locus of Control partially mediates on the impact of financial knowledge on financial management behaviour.